Peculiarities of regulatory and legal regulation of notarial activities of consular institutions - Kuzmenko, Oksana; Chorna, Viktoriia; Liutikov, Pavlo (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
This article discloses the specifics of the regulatory and legal regulation of the notarial activity of consular institutions.It was noted that ensuring the proper level of training and qualification of consular notaries. For this purpose, it is possible to carry out regular retraining and professional development of specialists, organize seminars and trainings.Attention is focused on the need to establish clear rules and procedures for notarial acts. Consular offices can create an internal document that contains clear instructions on how to perform different types of notarial acts. Ensuring the accessibility and convenience of the procedure for performing notarial acts. For this purpose, it is possible to consider the possibility of expanding the work schedule of consular institutions, making it possible to make an appointment for a visit, and introducing other tools to facilitate the procedure for performing notarial acts.It is necessary to establish a quality control system for the performance of notarial acts. To do this, you can create a feedback system with customers of services, conduct regular monitoring of the quality of service performance and study statistical data on the performance of notarial acts. The following steps can be proposed to expand the system of quality control of the performance of notarial acts by consular institutions of Ukraine:1) to introduce quality standards for the performance of notarial acts, which provide for the identification of quality criteria that take into account the best European practices and legislation and, accordingly, to determine the evaluation and assessment of the performance of notarial acts, which will include a rating of customer satisfaction, analysis of feedback on the performance of services, monitoring of compliance with established standards and other parameters;2) to develop a system of monitoring and reporting on the quality of the performance of notarial actions, which will provide for the collection, analysis and reporting of the results of the assessment of the quality of the performance of services;3) to develop and implement a satisfaction survey system for clients who have already used the services of the consular office and conduct an analysis to improve the quality of services;4) to introduce training courses once every 2 years for consular notaries and other employees on the quality of performance of notarial actions and compliance with standards;5) conduct an audit of consular notarial services once a year, in order to ensure compliance with standards and best practices;6) to establish responsibility for violation of norms defining the rules and procedure for providing consular services by consular institutions.